2009
DOI: 10.1002/chem.200801019
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transformation in Titania Nanocrystals by the Oriented Attachment Mechanism: The Role of the pH Value

Abstract: The oriented attachment (OA) mechanism has been investigated as an important process in the formation of anisotropic nanostructures such as depicted. The results showed that the control of a desired phase in this system may be attained by the control of OA mechanism through pH value, obtaining several morphologies.A new synthetic method for TiO(2) nanocrystals starting from metallic Ti and hydrogen peroxide was developed, in order to obtain minimal interferences to evaluate phase transformation in the system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
37
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 43 publications
3
37
0
2
Order By: Relevance
“…Among these methods, hydrothermal treatments appear to be potentially interesting in terms of morphological variations. [25][26][27][28][29][30][31] Guan et al reported a systematic study of ceria materials with different morphologies such as sphere, rods, and prisms via the hydrolysis of solutions containing Ce(NO 3 ) 3 and urea under hydrothermal conditions. 32 According to these authors, different morphologies were obtained by carefully adjusting the synthesis conditions such as salt concentration, temperature and synthesis time.…”
mentioning
confidence: 99%
“…Among these methods, hydrothermal treatments appear to be potentially interesting in terms of morphological variations. [25][26][27][28][29][30][31] Guan et al reported a systematic study of ceria materials with different morphologies such as sphere, rods, and prisms via the hydrolysis of solutions containing Ce(NO 3 ) 3 and urea under hydrothermal conditions. 32 According to these authors, different morphologies were obtained by carefully adjusting the synthesis conditions such as salt concentration, temperature and synthesis time.…”
mentioning
confidence: 99%
“…Ribiero et al, [31] recently reported the synthesis of titanium oxide nanocrystals, especially the rutile TiO 2 phase by a method based on peroxotitanium complex decomposition. A new synthetic method for TiO 2 nanocrystals starting from metallic Ti and hydrogen peroxide was developed by Ribiero et al, [32,33]. The results reported here are for nanophase anatase synthesis using a highly simplified one-pot method by conventional-and microwave-hydrothermal methods.…”
Section: Introductionmentioning
confidence: 90%
“…79,80 A concentração do precursor no reator hidrotermal possui um papel importante na fase e morfologia obtida. Isto acontece, pois a concentração é um fator chave em uma determinada cinética reacional, influenciando na mobilidade das partículas suspensas e na proporção de choques efetivos.…”
Section: Método Hidrotérmicounclassified
“…Em condições altamente alcalinas, o material obtido apresenta características tubulares. 80 Estruturas tubulares em nanoescala são interessantes devido à sua alta área superficial específica que é um fator decisivo em fotocatálise. Desde 1991, quando Iijima 86 reportou pela primeira vez a síntese de nanotubos de carbono, têm surgido diversas pesquisas de síntese de nanotubos, inclusive de semicondutores.…”
Section: Método Hidrotérmicounclassified